REVISITING THE SAFETY PROFILE OF TOPICAL CALCINEURIN INHIBITORS IN ATOPIC DERMATITIS: A SYSTEMATIC REVIEW AND META-ANALYSIS (2015–2026) IN THE CONTEXT OF PUBLIC HEALTH REGULATIONS - Złotnik, Anna; Krzysztofik, Kinga; Klamka, Antoni; Kawalec, Paulina; Bronikowski, Kamil; Ryszkowski, Maksymilian; Fornal, Krystian; Będkowska-Kuśmierek, Natalia; Zaborowska, Sabina; Pawlak, Paulina (International Journal of Innovative Technologies in Social Science, 2026)
Background. Atopic Dermatitis (AD) is a widespread, chronic inflammatory-related skin con-dition. Despite the effectiveness of topical calcineurin inhibitors (TCIs), their use is often limited by "TCI phobia" fueled by FDA "black box" warnings regarding potential oncological risks. These warnings were based on animal model studies conducted early in the development of the drug and systemic transplantation data. Aim. The aim of this study is to evaluate the oncological safety of TCIs in patients with atopic dermatitis by synthesizing the latest epidemiological evidence (2015–2026) and to discuss the implications of current public health regulator restrictions. Material and methods. A systematic review and meta-analysis adhered to the PRISMA 2020 guidelines. Databases (PubMed, Embase) were searched for cohort and case-control studies. Ten high-quality studies (Newcastle-Ottawa Scale ≥7) were selected. Statistical analysis was performed using JASP (Version 0.18.3) with a random-effects model (Restricted ML) to calcu-late pooled Relative Risks (RR) and evaluate heterogeneity (I2). Results. The quantitative synthesis included diverse age and geographical cohorts. The analysis revealed that TCI use is not associated with a statistically significant increase in the overall risk of malignancy (pooled RR = 0.97; 95% CI: 0.82–1.15; p = 0.529). Heterogeneity was non-existent (I2 = 0%). Long-term data (e.g., APPLES study) and large-scale pharmacovigilance reports (17 million FAERS records) confirmed no increased risk of lymphomas or hematopoietic malignancies. Conclusions. The oncological safety profile of TCIs is favorable and supported by pharmaco-kinetic evidence, that shows minor systemic absorption (< 1.0 ng/mL). Systemic cancer cases associated with TCI(s) are most likely historically attributed to protopathic bias. These findings strongly supports the removal of the "black box" warnings to reduce "TCI phobia" and improve therapeutic outcomes and quality of life for AD patients.